Quantitative in situ assay of salicylic acid in tobacco leaves using a genetically modified biosensor strain of Acinetobacter sp. ADP1. - Huang, W; Huang, L; Preston, G; Naylor, M; Carr, J; Li, Y; Singer, A; Whiteley, A; Wang, H (2006)
Salicylic acid (SA) plays important roles in plants, most notably in the induction of systemic acquired resistance (SAR) against pathogens. A non-destructive in situ assay for SA would provide new insights into the functions of SA in SAR and other SA-regulated phenomena. We assessed a genetically engineered strain of Acinetobacter sp. ADP1, which proportionally produces bioluminescence in response to salicylates including SA and methylsalicylate, as a reporter for salicylate accumulation in the apoplast of plant leaves. SA was measured quantitatively in situ in NN genotype tobacco (Nicotiana tabacum L. cv Xanthi-nc) leaves inoculated with tobacco mosaic virus (TMV). The biosensor revealed accumulation of apoplastic SA before the visible appearance of hypersensitive response (HR) lesions. When the biosensor was infiltrated into TMV-inoculated leaves displaying HR lesions at 90 and 168 h post-inoculation, salicylate accumulation was detected predominantly in tissues surrounding the lesions and in veins adjacent to HR lesions. These images are consistent with previous data demonstrating that SA accumulation occurs prior to and following the onset of visible HR lesions. We also used the biosensor to observe apoplastic SA accumulation in tobacco leaves inoculated with virulent and HR-eliciting strains of the bacterial plant pathogen Pseudomonas syringae. The work demonstrates that the Acinetobacter sp. ADP1 biosensor is a useful new tool to non-destructively assay salicylates in situ and to map their spatial distribution in plant tissues.